(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Fatigue is identified as an occupational health problem in developing countries and is a serious threat to human quality of life if fatigue becomes chronic and excessive. The problems faced by the juvenile fishing community are the risk of accidents and health problems and making the wrong decision in operating a boat can have serious consequences and even loss of life. The purpose of this activity is to provide socialization to the fishermen community regarding the introduction of fatique, causes of fatigue, prevention to avoid fatigue, and what to do during fatigue. The method used is lecture, discussion and question and answer. The implementation of community service is carried out in several stages including the preparation stage, field survey, implementation, and evaluation. The results obtained are the causes of fatigue in sailors, among others due to hard work, malnutrition, staying up late, drugs and alcohol. Fatigue is a condition of the body both physically and psychologically which causes fatigue and lack of concentration so that it is dangerous when working. Conclusions in preventing fatigue can be done by adhering to a rest schedule, adequate nutrition, proper clothing, sufficient drinking, danger alarms.